Biomineralization inspired 3D printed bioactive glass nanocomposite scaffolds orchestrate diabetic bone regeneration by remodeling micromilieu - Xu, Zeqian; Qi, Xuanyu; Bao, Minyue; Zhou, Tian; Shi, Junfeng; Xu, Zhiyan; Zhou, Mingliang; Boccaccini, Aldo R.; Zheng, Kai; Jiang, Xinquan (Bioactive Materials, 2023)
Type II diabetes mellitus (TIIDM) remains a challenging clinical issue for both dentists and orthopedists. By virtue of persistent hyperglycemia and altered host metabolism, the pathologic diabetic micromilieu with chronic inflammation, advanced glycation end products accumulation, and attenuated biomineralization severely impairs bone regeneration efficiency. Aiming to “remodel” the pathologic diabetic micromilieu, we 3D-printed bioscaffolds composed of Sr-containing mesoporous bioactive glass nanoparticles (Sr-MBGNs) and gelatin methacrylate (GelMA). Sr-MBGNs act as a biomineralization precursor embedded in the GelMA-simulated extracellular matrix and release Sr, Ca, and Si ions enhancing osteogenic, angiogenic, and immunomodulatory properties. In addition to angiogenic and anti-inflammatory outcomes, this innovative design reveals that the nanocomposites can modulate extracellular matrix reconstruction and simulate biomineralization by activating lysyl oxidase to form healthy enzymatic crosslinked collagen, promoting cell focal adhesion, modulating osteoblast differentiation, and boosting the release of OCN, the noncollagenous proteins (intrafibrillar mineralization dependent), and thus orchestrating osteogenesis through the Kindlin-2/PTH1R/OCN axis. This 3D-printed bioscaffold provides a multifunctional biomineralization-inspired system that remodels the “barren” diabetic microenvironment and sheds light on the new bone regeneration approaches for TIIDM.
CRIS-Team Scopus Importer:2023-02-24
Keywords: 3D printing; Biomineralization; Enzymatic cross-links; Sr-containing mesoporous bioactive glass nanoparticles; Type II Diabetes mellitus

Cerium doped dendritic mesoporous bioactive glass nanoparticles with bioactivity and drug delivery capability - Xu, Zhiyan; Keller, Emily; Beltrán, Ana M.; Zheng, Kai; Boccaccini, Aldo R. (Journal of Non-Crystalline Solids, 2023)
Dendritic mesoporous bioactive glass nanoparticles (DMBGNs) with unique three-dimensional structures are attracting increasing attention for biomedical applications. However, it is still challenging to tune the chemical composition of DMBGNs. In this work, we provide for the first time a feasible post-impregnation approach to incorporate metallic ions (Ca and Ce) into dendritic mesoporous silica nanoparticles, resulting in SiO2-CaO and SiO2-CaO-CeO2 (Ce-DMBGNs) without destroying the dendritic mesoporous topography. Both DMBGNs and Ce-DMBGNs were amorphous, negatively charged, with a hydrodynamic size of ∼200 nm. The synthesized DMBGNs and Ce-DMBGNs exhibited high bioactivity as evidenced by the rapid formation of hydroxyapatite (HA) after immersion in simulated body fluid (SBF) for 7 days. In addition, DMBGNs and Ce-DMBGNs showed high propolis loading efficiency and sustained release behavior. The results suggest that the developed Ce-DMBGNs have the potential to be used as a delivery vehicle of therapeutic ions and drugs in bone regeneration applications.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Bioactive glass; Bioactivity; Cerium; Dendritic mesoporous nanoparticle; Drug delivery

Electrically conductive coatings in tissue engineering - Kohestani, Abolfazl Anvari; Xu, Zhiyan; Bastan, Fatih Erdem; Boccaccini, Aldo R.; Pishbin, Fatemehsadat (Acta Biomaterialia, 2024)
Recent interest in tissue engineering (TE) has focused on electrically conductive biomaterials. This has been inspired by the characteristics of the cells’ microenvironment where signalling is supported by electrical stimulation. Numerous studies have demonstrated the positive influence of electrical stimulation on cell excitation to proliferate, differentiate, and deposit extracellular matrix. Even without external electrical stimulation, research shows that electrically active scaffolds can improve tissue regeneration capacity. Tissues like bone, muscle, and neural contain electrically excitable cells that respond to electrical cues provided by implanted biomaterials. To introduce an electrical pathway, TE scaffolds can incorporate conductive polymers, metallic nanoparticles, and ceramic nanostructures. However, these materials often do not meet implantation criteria, such as maintaining mechanical durability and degradation characteristics, making them unsuitable as scaffold matrices. Instead, depositing conductive layers on TE scaffolds has shown promise as an efficient alternative to creating electrically conductive structures. A stratified scaffold with an electroactive surface synergistically excites the cells through active top-pathway, with/without electrical stimulation, providing an ideal matrix for cell growth, proliferation, and tissue deposition. Additionally, these conductive coatings can be enriched with bioactive or pharmaceutical components to enhance the scaffold's biomedical performance. This review covers recent developments in electrically active biomedical coatings for TE. The physicochemical and biological properties of conductive coating materials, including polymers (polypyrrole, polyaniline and PEDOT:PSS), metallic nanoparticles (gold, silver) and inorganic (ceramic) particles (carbon nanotubes, graphene-based materials and Mxenes) are examined. Each section explores the conductive coatings’ deposition techniques, deposition parameters, conductivity ranges, deposit morphology, cell responses, and toxicity levels in detail. Furthermore, the applications of these conductive layers, primarily in bone, muscle, and neural TE are considered, and findings from in vitro and in vivo investigations are presented. Statement of significance: Tissue engineering (TE) scaffolds are crucial for human tissue replacement and acceleration of healing. Neural, muscle, bone, and skin tissues have electrically excitable cells, and their regeneration can be enhanced by electrically conductive scaffolds. However, standalone conductive materials often fall short for TE applications. An effective approach involves coating scaffolds with a conductive layer, finely tuning surface properties while leveraging the scaffold's innate biological and physical support. Further enhancement is achieved by modifying the conductive layer with pharmaceutical components. This review explores the under-reviewed topic of conductive coatings in tissue engineering, introducing conductive biomaterial coatings and analyzing their biological interactions. It provides insights into enhancing scaffold functionality for tissue regeneration, bridging a critical gap in current literature.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Cellular response; Conductive coating; Electrical stimulation; Scaffold; Tissue engineering

Extracellular and intracellular effects of bioactive glass nanoparticles on osteogenic differentiation of bone marrow mesenchymal stem cells and bone regeneration in zebrafish osteoporosis model - Meng, Li; Zhao, Panpan; Jiang, Yucheng; You, Jiawen; Xu, Zhiyan; Yu, Kui; Boccaccini, Aldo R.; Ma, Junqing; Zheng, Kai (Acta Biomaterialia, 2024)
Bioactive glass nanoparticles (BGNs) are well-recognized multifunctional biomaterials for bone tissue regeneration due to their capability to stimulate various cellular processes through released biologically active ions. Understanding the correlation between BGN composition and cellular responses is key to developing clinically usable BGN-based medical devices. This study investigated the influence of CaO content of binary SiO2-CaO BGNs (CaO ranging from 0 to 10 mol%) on osteogenic differentiation of rat bone marrow mesenchymal stem cells (rBMSCs) and in vivo bone regeneration in zebrafish osteoporosis model. The results showed that BGNs could promote osteogenic differentiation of rBMSCs by indirectly releasing active ions or directly interacting with rBMSCs by internalization. In both situations, BGNs of a higher CaO content could promote the osteogenic differentiation of rBMSCs to a greater extent. The internalized BGNs could activate the transcription factors RUNX2 and OSX, leading to the expression of osteogenesis-related genes. The results in the zebrafish osteoporosis model indicated that the presence of BGNs of higher CaO contents could enhance bone regeneration and rescue dexamethasone-induced osteoporosis to a greater extent. These findings demonstrate that BGNs can stimulate osteogenic differentiation of rBMSCs by releasing active ions or internalization. A higher CaO content facilitates osteogenesis and bone regeneration of zebrafish as well as relieving dexamethasone-induced osteoporosis. The zebrafish osteoporosis model can be a potent tool for evaluating the in vivo bone regeneration effects of bioactive materials. Statement of significance: Bioactive glass nanoparticles (BGNs) are increasingly used as fillers of nanocomposites or as delivery platforms of active ions to regenerate bone tissue. Various studies have shown that BGNs can enhance osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) by releasing active ions. However, the correlation between BGN composition and cellular responses and in vivo bone regeneration effect has still not been well investigated. Establishment of a suitable in vivo animal model for investigating this correlation is also challenging. The present study reports the influence of CaO content in binary SiO2-CaO BGNs on osteogenic differentiation of BMSCs extracellularly and intracellularly. This study also demonstrates the suitability of zebrafish osteoporosis model to investigate in vivo bone regeneration effect of BGNs.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Bioactive glass; Bone regeneration; Cellular uptake; Osteoporosis; Zebrafish model

Mucin Coatings Establish Multifunctional Properties on Commercial Sutures - Gürer, Ufuk; Fan, Di; Xu, Zhiyan; Nawaz, Qaisar; Baartman, Jorrit; Boccaccini, Aldo R.; Lieleg, Oliver (ACS Applied Bio Materials, 2025)
During the wound healing process, complications such as bacterial attachment or inflammation may occur, potentially leading to surgical site infections. To reduce this risk, many commercial sutures contain biocides such as triclosan; however, this chemical has been linked to toxicity and contributes to the occurrence of bacterial resistance. In response to the need for more biocompatible alternatives, we here present an approach inspired by the innate human defense system: utilizing mucin glycoproteins derived from porcine mucus to create more cytocompatible suture coatings with antibiofouling properties. By attaching manually purified mucin to commercially available sutures through a simple and rapid coating process, we obtain sutures with cell-repellent and antibacterial properties toward Gram-positive bacteria. Importantly, our approach preserves the very good mechanical and tribological properties of the sutures while offering options for further modifications: the mucin matrix can either be condensed for controlled localized drug release or covalently functionalized with inorganic nanoparticles for hard tissue applications, which allows for tailoring a commercial suture for specific biomedical use cases.
CRIS-Team Scopus Importer:2025-03-21
Keywords: antibacterial; bioactive glass; biopolymer; drug release; surgical site infection

Mussel-Inspired Polydopamine Composite Mesoporous Bioactive Glass Nanoparticles: An Exploration of Potential Metal-Ion Loading Platform and In Vitro Bioactivity - Sui, Baiyan; Xu, Zhiyan; Xue, Zhiyu; Xiang, Yong; Zhou, Tian; Beltrán, Ana M.; Zheng, Kai; Liu, Xin; Boccaccini, Aldo R. (ACS Applied Materials and Interfaces, 2023)
Exploring new approaches to realize the possibility of incorporating biologically active elements into mesoporous silicate bioactive glass nanoparticles (MBG NPs) and guaranteeing their meso- structural integrity and dimensional stability has become an attractive and interesting challenge in biomaterials science. We present a postgrafting strategy for introducing different metal elements into MBG NPs. This strategy is mediated by polydopamine (PDA) coating, achieving uniform loading of copper or copper-cobalt on the particles efficiently and ensuring the stability of MBG NPs in terms of particle size, mesoporous structure, and chemical structure. However, the PDA coating reduced the ion-binding free energy of the MBG NPs for calcium and phosphate ions, resulting in the deposition of minimal CaP clusters on the PDA@MBG NP surface when immersed for 7 days in simulated body fluid, indicating the absence of hydroxyapatite mineralization.
CRIS-Team Scopus Importer:2023-07-07
Keywords: biomineralization; mesoporous bioactive glass; metal-ion loading; molecular dynamics simulation; polydopamine coating

Organic solvent-free synthesis of dendritic mesoporous bioactive glass nanoparticles with remineralization capability - Han, Xiao; Erkan, Aleyna; Xu, Zhiyan; Chen, Yaming; Boccaccini, Aldo R.; Zheng, Kai (Materials Letters, 2022)
Dendritic mesoporous bioactive glass nanoparticles (DMBGNs) are emerging biomaterials for various biomedical applications. However, their synthesis usually involves extensive volatile organic solvents, causing significant environmental and economic issues. We report an organic solvent-free strategy to produce DMBGNs, in which cationic and anionic surfactants were used as dual templates free of organic solvents to assemble silicate nanoparticles before incorporation of Ca by impregnation. The Ca incorporation did not affect the dendritic mesoporous structure of the nanoparticles. DMBGNs exhibited remineralization capacity as evidenced by hydroxyapatite (HA) formation after soaking in simulated body fluid (SBF). The results indicate the feasibility of the proposed organic solvent-free, two-step strategy for producing DMBGNs highlighting also the great potential of DMBGNs as remineralization agents.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Bioactive glasses; Biomaterials; Green synthesis; Nanoparticles; Remineralization

Sol-gel derived B2O3-CaO borate bioactive glasses with hemostatic, antibacterial and pro-angiogenic activities - Zheng, Kai; Bider, Faina; Monavari, Mahshid; Xu, Zhiyan; Janko, Christina; Alexiou, Christoph; Beltrán, Ana M.; Boccaccini, Aldo R. (Regenerative Biomaterials, 2024)
Sol-gel borate bioactive glasses (BGs) are promising ion-releasing biomaterials for wound healing applications. Here, we report the synthesis of a series of binary B2O3-CaO borate BGs (CaO ranging from 50 to 90 mol%) using a sol-gel-based method. The influence of CaO content in B2O3-CaO borate BG on morphology, structure and ion release behavior was investigated in detail. Reduced dissolution (ion release) and crystallization could be observed in borate BGs when CaO content increased, while the morphology was not significantly altered by increasing CaO content. Our results evidenced that the ion release behavior of borate BGs could be tailored by tuning the B2O3/CaO molar ratio. We also evaluated the in vitro cytotoxicity, hemostatic, antibacterial and angiogenic activities of borate BGs. Cytocompatibility was validated for all borate BGs. However, borate BGs exhibited composition-dependent hemostatic, antibacterial and angiogenic activities. Generally, higher contents of Ca in borate BGs facilitated hemostatic activity, while higher contents of B2O3 were beneficial for pro-angiogenic activity. The synthesized sol-gel-derived borate BGs are promising materials for developing advanced wound healing dressings, given their fast ion release behavior and favorable hemostatic, antibacterial and angiogenic activities.
CRIS-Team Scopus Importer:2024-02-02
Keywords: borate glasses; glass composition; sol-gel processing; wound healing

Surface engineering of mesoporous bioactive glass nanoparticles with bacteriophages for enhanced antibacterial activity - Meng, Xiangjun; Xu, Zhiyan; Wang, Chen; Patitz, Jennifer; Boccaccini, Aldo R.; Burkovski, Andreas; Zheng, Kai (Colloids and Surfaces B: Biointerfaces, 2024)
Binary SiO2-CaO mesoporous bioactive glass nanoparticles (MBGNs) are multifunctional biomaterials able to promote osteogenic, angiogenic, and immunomodulatory activities. MBGNs have been applied in a variety of tissue regeneration strategies. However, MBGNs lack strong antibacterial activity and current strategies (loading of antibacterial ions or antibiotics) toward enhanced antibacterial activity may cause cytotoxicity or antibiotic resistance. Here we engineered MBGNs using bacteriophages (phages) to enhance the antibacterial activity. Salmonella Typhimurium (S. T) phage PFPV25.1 that can infect Salmonella enterica serovar Typhimurium strain LT2 was used as a model phage to engineer MBGNs. MBGNs were first modified with amine groups to enhance the affinity between phages and MBGNs surfaces. Afterward, the physicochemical and antibacterial activity of phage-engineered MBGNs was evaluated. The results showed that S. T phage PFPV25.1 was successfully bound onto MBGNs surfaces without losing their bioactivity. A higher quantity of phages could be bounded onto amine-functionalized MBGNs than onto non-functionalized MBGNs. Phages on amine-functionalized MBGNs exhibited higher antibacterial activity. The stability test showed that phages could remain on amine-functionalized MBGNs for over 28 days. This work provides valuable information on developing phage-modified MBGNs as a new and effective antibacterial system for biomedical applications.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Bacterial control; Bioactive glass; Nanoparticles; Phage; Samonella Typhimurium

Tailoring the adhesion of electrophoretic chitosan/bioactive glass coatings by the combined surface pre-treatments of Ti substrates - Kowalczyk, Agnieszka; Sotniczuk, Agata; Kuczyńska-Zemła, Donata; Pura, Jarosław; Xu, Zhiyan; Boccaccini, Aldo R.; Garbacz, Halina (Surface & Coatings Technology, 2024)
Composite chitosan/bioactive glass coatings developed by electrophoretic deposition (EPD) attract researchers' attention owing to their advantageous effect on the biological and corrosion responses of commonly used biomedical materials. However, fabricating a uniform coating with satisfactory adhesion to the biomaterials substrate is challenging, because chitosan and bioglass particles having different mobilities during the EPD process. Typically, attempts are made to improve adhesion by manipulating the EPD parameters. This work presents an alternative approach that involves combined mechanical and chemical pre-treatments of the Ti substrate. The surface pre-treatment procedure included shot peening and the following variants of acid etching: (i) HF etching, (ii) NaOH etching, and (iii) HF and NaOH etching. Shot peening followed by etching in HF and NaOH significantly improved the adhesion of the EPD coating. It was found that this effect was due to the development of a highly hydrophilic surface with micro- and nano-scale roughness.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Bioactive glass; Chitosan; Electrophoretic deposition; Surface topography; Titanium